Positive effects of parent–child group emotional regulation and resilience training on nonsuicidal self-injury behavior in adolescents: a quasi-experimental study - Cheng, Junxiang; Zhao, Juan; Song, Baoli; Han, Hong; Liu, Na; Chen, Yangjie; Liu, Xiaomei; Dong, Yue; Bian, Weina; Liu, Zhifen; Han, Shifan (Frontiers in Psychiatry, 2024)
Background: Nonsuicidal self-injury (NSSI) among adolescents is a growing global concern. However, effective interventions for treating NSSI are limited.A 36-week quasi-experimental study design of parent-child group resilience training (intervention group) for adolescents aged 12-17 years was used and compared with treatment-as-usual (control group). The primary endpoint was the frequency of NSSI assessed with the Ottawa Self-Injury Inventory (OSI), and the secondary endpoints were the levels of depression, hope, resilience, and family adaptability and cohesion as assessed by the 24-item Hamilton depression rating scale (HAMD-24), Herth Hope Scale (HHS), Connor-Davidson Resilience Scale (CD-RISC), and Family Adaptability and Cohesion Evaluation Scale, second edition (FACES-II-CV), respectively.Result: A total of 118 participants completed the trial. Both groups showed a significant reduction in NSSI frequency after 12, 24, and 36 weeks of intervention (p < 0.05), although the intervention group did not differ significantly from the control group. After 12, 24, and 36 weeks of intervention, the CD-RISC, HHS, HAMD-24, and FACES-II-CV scores in the intervention and control groups improved over baseline (p < 0.05). Furthermore, the intervention group had higher scores on the CD-RISC, HHS, and FACES-II-CV and lower scores on the HAMD-24 than the control group after 12, 24, and 36 weeks of intervention (p < 0.05).Parent-child group emotional regulation and resilience training showed promise as treatment options for NSSI among adolescents, leading to increased hope, resilience, and improved family dynamics among NSSI teens. Moreover, NSSI frequency significantly decreased in the intervention group compared to baseline.